2016
DOI: 10.17559/tv-20140928112417
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of energy usage and emissions on plug-in and hybrid electric vehicle

Abstract: Preliminary noteOne of the major issues in automotive industry is to develop hybrid electric vehicles (HEVs) as the prime candidate for improving fuel efficiency and emissions reduction. This study addresses the impact of an actual drive pattern and control strategy on the conventional and plug-in hybrid electric vehicles (PHEV). In the first step the development procedure of driving cycle for real condition is proposed. Then effects of driving pattern and energy management strategy as the main factors, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In areas where the price of power is greater during peak hours and cheaper during off-peak hours, this technique can be highly beneficial. By avoiding power use at peak times and charging the BRV battery during off-peak times, the system saves money for the customer [6]. The machine learning system learns about the appropriate usage of batteries depending on the existing power tariffs and the household load.…”
Section: Introductionmentioning
confidence: 99%
“…In areas where the price of power is greater during peak hours and cheaper during off-peak hours, this technique can be highly beneficial. By avoiding power use at peak times and charging the BRV battery during off-peak times, the system saves money for the customer [6]. The machine learning system learns about the appropriate usage of batteries depending on the existing power tariffs and the household load.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that an HEV contains an internal combustion engine and a fuel tank, and an electric motor and an ESS (battery). In summary, they stated that in an HEV, they used two drivers for the powertrain [3]. In conventional vehicles, kinetic energy is lost as heat energy in the lining in the case of sudden braking or downhill idling.…”
Section: Introductionmentioning
confidence: 99%
“…The sustainability of the transport system is increasingly becoming a top-priority objective of public administrations at all levels. At strategic levels, these policy objectives are mainly driven by international commitments to reducing greenhouse gas (GHG) emissions [3][4][5].…”
Section: Introductionmentioning
confidence: 99%